Review of the Mechanistic and Structural Assessment of Binders in Electrodes for Lithium-Ion Batteries - Yoon, Hyungsub; Behera, Promoda; Lim, Sooman; Yun, Tae Gwang; Hwang, Byungil; Cheong, Jun Young (International Journal of Energy Research, 2024)
With the continual increase in CO2 levels and toward a sustainable society, developing high-performance lithium-ion batteries (LIBs) is crucial. A suitable electrode design is the key to enhancing the quality of battery cells (e.g., cycle retention characteristics and rate capabilities), and the binder plays an important role in providing sufficient adhesion between the active material, conductive agent, and current collector. Despite significant advances in the development of novel binder materials and solutions that can be employed as anode and cathode materials, careful investigations and summaries of the assessment methods for binder materials remain lacking. In this review, we examine the different analyses used to assess the quality of binder materials and how they help in assessing the quality of the electrode design. In addition, future perspectives on binder assessment are presented, which can be applied to future research directed toward binder development for advanced LIBs or post-LIBs.
Keywords: Battery cells; Binder (material); Electrode design; High-performance lithium-ion batteries; Mechanistics; Rate capabilities; Retention characteristics; Retention rate; Structural assessments; Sustainable society